Full-field optical coherence tomography - Ford, Helen D.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2005)
To eliminate mechanical scanning in the probe head of an endoscopic OCT system, we propose the use of an imaging fibre bundle for probe beam delivery. Each fibre in the bundle addresses a Fizeau interferometer formed between the bundle end and the sample, allowing acquisition of information across a plane with a single measurement. Depth scanning components are now contained within a processing interferometer external to a completely passive endoscope probe. The technique has been evaluated in our laboratory for non-biological samples, including glass/air and mirrored/air interfaces. Images resulting from these experiments are presented. The potential of the system is assessed, with reference to SNR performance and acquisition speed.